FAKTOR-FAKTOR YANG MEMENGARUHI SIKAP DAN MINAT PEMBELIAN MILENIAL TERHADAP ASURANSI JIWA - Everlin, Shierla; Senastri Dahlan, Kandi Sofia (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This research purpose is to identify factors that influence attitudes and millenial’s purchase intention toward life insurance by focusing on the areas of financial literacy, perceived trust, and demographics. Design/methodology/approach- The research method is quantitative and questionnaires were collected and processed using variance-based structural equation modeling (SEM). Findings- The results showed that financial literacy, perceived trust, and demographics had a significant and positive influence on millennial attitudes and interests. The perceived trust turns out to act as the strongest predictor in predicting attitudes towards life insurance. Implications- The implications of research with a simple model and research instruments that do not involve interviews limit the scope of the research and generalization of findings. Keywords: attitude, purchase intention, financial literacy, perceived trust, demographic, life insurance